The Influence of Fear of Failure and Entrepreneurship Education on Social Entrepreneurship Intention - Pribadi, Henry (Jurnal Entrepreneur dan Entrepreneurship (JEE), 2025)
This paper examines the relationship between the intention to create a social enterprise and inhibiting factors, particularly in the context of the fear of failure, among undergraduate students enrolled in entrepreneurship-focused curricula. The study aims to investigate how constraining factors, such as the fear of failure, influence an individual's intention to start a business. The relationship between entrepreneurship education and curriculum will help mitigate the inhibiting effect of the fear of failure factors, which is also examined. Senior year undergraduate students majoring in business at Universitas Prasetiya Mulya were selected as the primary focus of the study, considering that the curriculum is heavily focused on creating entrepreneurs. The method used is a quantitative research method, specifically employing a survey-based approach, analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show no significant relationship between social entrepreneurship intention and fear of failure, whereas the relationship between fear of failure factors and perceived entrepreneurial education exhibits a strong positive correlation. Entrepreneurship education and social entrepreneurship intention show a significant positive relationship as predicted. On an entrepreneurship-focused campus, fear of failure does not significantly influence students' decisions to become entrepreneurs in the future.